Concave gold nanocube assemblies as nanotraps for surface-enhanced Raman scattering-based detection of proteins1. Issue 8 (28th February 2015) - Matteini, Paolo; de Angelis, Marella; Ulivi, Lorenzo; Centi, Sonia; Pini, Roberto
<x xml:space="preserve">Abstract</x> The SERS fingerprint of a protein is revealed once entrapped in a nanohole between assembled gold nanocubes.